027 Percutaneous coronary intervention in octogenarians: results from a high volume centre. (16th May 2012) - Showkathali, R; Boston-Griffiths, E; Patel, H; Ramoutar, A; Davies, J; Kabir, A; Gamma, R; Jagathesan, R; Sayer, J; Clesham, G; Kelly, P; Aggarwal, R
Abstract : Aims: Octogenarians constitute a fast growing group of patients referred for percutaneous coronary intervention (PCI) for stable angina and acute coronary syndromes (ACS). However, there are limited outcome data for PCI in this group. We evaluated the outcome of PCI in patients aged ≥80 years and compared them with younger patients treated in our centre. Methods: We analysed all patients aged ≥80 years who underwent PCI in our unit between September 2009 and December 2010. Prospectively entered data were obtained from our dedicated cardiac service database system (Philips CVIS). Mortality data were obtained from the summary care record (SCR) database. Follow-up data were obtained from patients' respective district general hospitals and general practitioners' medical records. We defined major bleeding as anyone requiring at-least one unit of red cell transfusion. Results: Of the 2931 patients who underwent PCI in our unit during the study period, 401 (13.7%) patients were ≥80 years of age. Out of this 163 (40.6%) had primary PCI (PPCI) for STEMI, 120 (29.9%) had PCI for non-ST elevation ACS (NSTEACS) and 118 (29.4%) had PCI for stable angina. Of the 2530 patients in the younger cohort (<80 years) who had PCI, 765 (30.2%) had PPCI, 739 (29.2%) had PCI for NSTEACS and 1026 (40.6%) had PCI for stable angina. The demographic and procedural data of octogenarians are compared with younger patients (Abstract 027 table 1 ). The clinical outcomes for octogenarians are shown in Abstract 027 table 2 . The total 30-day mortality for patients aged ≥ 80 years was 8.7% compared with a mortality rate of 1.3% for those aged <80 years (p<0.0001). This highly significant mortality difference related almost entirely to a fivefold higher mortality in patients aged ≥80 years undergoing PPCI compared with younger patients (Abstract 027 figure 1 ). Conclusion: In this consecutive series from a high volume tertiary centre, patients aged ≥80 years undergoing PCI have 30-day mortality rates comparable with younger patients treated for stable angina or NSTEACS. Further studies are required to refine treatment strategies in unselected patients aged ≥80 years undergoing PPCI for STEMI.